ANALISIS ANGGARAN PENDAPATAN SEBAGAI ALAT UKUR PENCAPAIAN BONUS PADA GERAI TUPPERWARE GUMUK MAS PRINGSEWU PADA TAHUN 2014 – 2016 - Septi Utami; Taufiqurarahman Taufiqurarahman (Jurnal Ilmiah Ekonomi Manajemen: Jurnal Ilmiah Multi Science, 2017)
The company will plan and control what is deemed important in the process of achieving the objectives, planning and controlling activities is called by arranging the revenue budget. The income budget in the current period is usually based on the realization of the revenue achieved in the previous period. If the realization of this income continues to increase in each operational period the company will receive a bonus, and if what happens is the opposite, then the bonus on income will not be given.The problem in this study is the formulation of fixed revenue budget that simultaneously with the movement of bonuses that tend to decline. The purpose of this study is Want to know the Description of the Revenue Budget as a measurement of the Achievement of Bonus at Tupperware Gumuk Mas Pringsewu outlet in 2014-2016.This study used the method of documentation research, interviews, and observation in order to obtain the necessary data, both primary data and secondary data owned by the research site.Based on the results of the Budget Analysis of Income as a Measure of Bonus Achievement, it can be seen that the total results of this study shows the percentage of growth analysis of revenue realization of 12.90%. As for the total value of the percentage analysis of bonus growth before taxes amounted to 43,93%, this Tupperware Gumuk Mas Pringsewu Gerai assessed not maximal in realizing revenue. As for the total value of the calculation of the analysis of income variance analysis as a means of measuring the achievement of bonus assessed fadalah of 245,42%. This can be used as evidence that the income budget can be used as a means of achieving the bonus, while the average research result from Pph contribution analysis on the after-tax bonus is low because it is from the beginning has automatically determined the amount of tax rate by the central company that is equal to 3, 50%.